Protective effects of Tualang honey on bone structure in experimental postmenopausal rats (Clinics, 2012)
OBJECTIVE: The objective of this study was to evaluate the effects of Tualang honey on trabecular structure and compare these effects with those of calcium supplementation in ovariectomized rats. METHODS: Forty female, Sprague-Dawley rats were randomly divided into five groups (n =8): four controls and one test arm. The control arm comprised a baseline control, sham-operated control, ovariectomized control, and ovariectomized calcium-treated rats (receiving 1% calcium in drinking water ad libitum). The test arm was composed of ovariectomized, Tualang honey-treated rats (received 0.2 g/kg body weight of Tualang honey). Both the sham-operated control and ovariectomized control groups received vehicle treatment (deionized water), and the baseline control group was sacrificed without treatment. RESULTS: All rats were orally gavaged daily for six weeks after day one post-surgery. The bone structural analysis of rats in the test arm group showed a significant increase in the bone volume per tissue volume (BV/TV), trabecular thickness (Tb.Th) and trabecular number (Tb.N) and a significant decrease in inter-trabecular space (Tb.Sp) compared with the ovariectomized control group. The trabecular thickness (Tb.Th) in the test arm group was significantly higher compared with the ovariectomized-calcium treated group, and the inter-trabecular space (Tb.Sp) in the test arm group was significantly narrower compared with the ovariectomized-calcium treated group. CONCLUSION: In conclusion, ovariectomized rats that received Tualang honey showed more improvements in trabecular bone structure than the rats that received calcium.